Réponses

2013-10-13T21:16:43+02:00
(6x+3) (2x+7) + (8x+1) (9x+5)
=12x²+42x+6x+21+72x²+40x+9x+5
=84x²+97x+26

(7x+2) (6x-1) + (4x-9) (3x+2) 
=42x²-7x+12x-2+12x²+8x-27x-18
=54x²-14x-20

(2x+5) (6x-7) - (9x-5) (4x+1) 
=12x²-14x+30x-35-(36x²+9x-20x-5)
=12x²-14x+30x-35-36x²-9x+20x+5
= -24x²+27x-30

(10x-5) (2x-1) - (8x-3) (7x-2) 
=20x²-10x-10x+5-(56x²-16x-21x+6)
=20x²-10x-10x+5-56x²+16x+21x-6
= -36x²+17x-1

(4-5x) (3x-8) - (5-x) (2x-7)
=12x-32-15x²+40x-(10x-35-2x²+7x)
=12x-32-15x²+40x-10x+35+2x²-7x
= -13x²+35x+3
2013-10-13T21:23:18+02:00
(6x+3) (2x+7) + (8x+1) (9x+5)
(12x² +42x + 6x + 21) + (72x² + 40x +9x +5)
= 12x² + 48x +21 + 72x² + 49x +5
= 84x² + 97x + 26
(7x+2) (6x-1) + (4x-9) (3x+2)
(42x²  - 7x +12x -2) + ( 12x² +8x - 27x -18)
= 42x² +5x -2 + 12x² - 19x -18
= 54x² - 14x -20
(2x+5) (6x-7) - (9x-5) (4x+1)
= (12x² -14x +30x -35) - (36x² +9x -20x -5)
= 12x² + 16x -35 - 36x² -9x + 20x + 5
= -24x² + 27x  - 30
(10x-5) (2x-1) - (8x-3) (7x-2)
(20x² - 10x  - 10x +5) - ( 56x² - 16x -21x +6)
=20x² -20x +5 - 56x² +16x +21x -6
= - 36x² + 17x -1
(4-5x) (3x-8) - (5-x) (2x-7)

12x - 32 - 15x² +40x - (10x -35 -2x² +7x)
= -15x²  +52x -32 - 10x +35 +2x² -7x
= -13x² +35x - 4
je ne vois pas l'erreur , merci de me dire où elle est.
(4-5x) (3x-8) - (5-x) (2x-7)
12x - 32 - 15x² +40x - (10x -35 -2x² +7X)
= -15x² +52x -32 - 10x +35 +2x² -7X
= -13x² +35x +3
le x du 7 que tu as oublié
merci j'ai corrigé
dr